The Plurality of Beings And The Oneness of Khaliq (A Study of The Conception of The Sufis) - Muh. Akmal Shafar; Hamzah Harun Ar-Rasyid; Amiril Mueminin (Lembaga Sembilan Tiga Community, 2023)
Sufism is one of the intellectual property that Islam has, its presence carries its own color and echo, although its presence is often debated and not a few groups consider sufis to be ignorant. However, the contribution of thought from sufistic figures undeniably had a great influence in Islamic discourse, one of which was the sufi view of the plurality of beings. Thus the purpose of this study is to reveal the sufi thinking towards the plurality of makhluk and the oneness of Khaliq. The research methodology used is a qualitative descriptive method. This research found that sufis were divided into two groups, namely the Sufism Falsafi (Theosophy) group and the Sufism Akhlaki group. It is called the falsafi sufism group because it combines reason and intuition (Dzauq), The figures are Al-Hallaj, Ibn 'Arabi and Abu Yazid Al-bustomi. The group thought of Sufism Falsafi, namely Fana, Baqa, and ittihad, was initiated by Abu Yazid Al-Bustomi, Hulul by Al-hallaj, and Wahdatul Wujud by Ibn 'Arabi.